Thoracoscopy with Concurrent Esophagoscopy for Persistent Right Aortic Arch in 9 Dogs. Issue 8 (12th October 2016) - Townsend, Sarah; Oblak, Michelle L.; Singh, Ameet; Steffey, Michele A.; Runge, Jeffrey J.
Abstract : Objective: To report the diagnosis, treatment, and short‐term outcome in dogs with suspected persistent right aortic arch (PRAA) undergoing thoracoscopy with concurrent esophagoscopy. Study Design: Multi‐institutional retrospective case series. Animals: Dogs with suspected PRAA (n=9). Methods: Medical records were reviewed from 2012 to 2016. Dogs undergoing thoracoscopy for PRAA at 3 referral hospitals were included. Signalment, clinical signs, diagnostic imaging, anesthesia protocol (including the use of one‐lung ventilation), surgical approach, complications, and short‐term outcome were recorded. Dogs underwent a left‐sided intercostal thoracoscopic approach with concurrent intraoperative esophagoscopy. The ligamentum arteriosum (LA) and constricting fibers were divided using a vessel‐sealing device using a 3 or 4 port thoracoscopy technique. Visualization and dissection of the LA was aided by transesophageal illumination by esophagoscopy. Results: Thoracoscopy confirmed PRAA in 9 dogs, with an aberrant left subclavian artery (LS) identified in 5 dogs. Major complications occurred in 2 dogs: postoperative hemorrhage from the LS and esophageal perforation, which resulted in euthanasia. Median follow‐up was 250 days (range, 56–1, 595). Regurgitation resolved in 4 of 8 surviving dogs. One dog had recurrence of regurgitation 1, 450 days postoperatively, esophageal compression by the LS was identified, and regurgitation resolved following LS transection. Conclusion: Esophagoscopy aided identification and dissection of the LA in all cases. Due to the potential for the LS to cause clinical esophageal constriction postoperatively, a recommendation for LS transection may be warranted. Vascular clips can also be considered as an alternative for vessel ligation to avoid complications associated with vessel‐sealing device use.